THE EFFECT OF FINANCIAL LITERACY ON PERFORMANCE OF SMALL AND MEDIUM ENTERPRISES IN MUKONO - MARK OMARA OCHAN (Uganda Christian University, 2025)
The small and medium enterprises sector has a crucial role in the economy of Uganda and highly contributing to employment, economic growth and income generation. Small and medium enterprises in mukono operate in sectors like retail, manufacturing, agriculture and services though most of them face challenges that hinder their growth and sustainability. Low financial literacy among small and medium enterprises owners and managers is one of the key blocks affecting budgeting, recordkeeping, investment decision, debt management and the whole financial planning aspect. This study investigated the effect of financial literacy on performance of small and medium enterprises in mukono district between 2019 to 2024. A research (descriptive) was conducted targeting 150 small and medium enterprises, with a random stratified random sampling of 109 owners and managers. All the data was collected using questionnaires and analysed using descriptive and inferential statistics. The study indicates a moderate financial literacy among small and medium enterprise owners and managers with strong knowledge of budgeting and planning but moderate financial behaviours and attitudes. Small and medium enterprises performance was also relatively moderate and the sustainability is rated higher than profitability and growth. Nevertheless, a positive relationship was observed between financial literacy and business performance which shows that higher financial knowledge enables managers and owners to make informed decisions, manage resources effectively, access finance and improve overall outcomes. The study summarizes that enhancing financial literacy is important for improving small and medium enterprise profitability, growth and sustainability. Recommendations basically include practical training workshops, targeted financial education programs and policy interventions by government and financial institutions. The research highly contributes to the understanding of financial literacy’s importance in small and medium enterprise performance and the countries development.
Undergraduate Research